PERAN HUMAS PT PLN (PERSERO) UNIT INDUK WILAYAH MALUKU DAN MALUKU UTARA TERHADAP SOSIALISASI PEMAKAI - Marleen Muskita; Putry Andris; Jimmy Purwata Mangasih Sirait (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
The increasing times and technological developments encourage people to meet important needs, apart from basic needs such as clothing, food and shelter, electricity is one of the important needs that people use to complete work or daily activities. PT PLN (Persero) Maluku and North Maluku Region has the task of providing electricity for the public interest, so that the supply of electricity can meet consumer needs. Be it electricity needs in households, industry, offices, social, business, or street lighting. This thesis examines the role of PT PLN (Persero) Public Relations in the Maluku and North Maluku Regions in the socialization of electricity users in Ambon City. The method used in this research is a qualitative method. Research data was collected through interviews, observation and documentation. The theory used in this thesis is Stakeholder Theory. The results of this research are the public relations of PT. PLN PLN (Persero) for the Maluku and North Maluku Regions, namely carrying out all outreach activities, both directly and indirectly. Public Relations acts as a communicator who disseminates information about programs or recapitulates the results of complaint reports through social media, radio, websites or digital platforms. Public Relations is also a mediator and resource person who also forms media relations regarding programs from PT PLN (Persero), the parent unit of the Maluku and North Maluku Regions.